PENILAIAN KINERJA DI ERA COVID (Study Kasus di Dinas Sosial Provinsi Sulawesi Selatan) - Andriani, Andi Dewi; Kusumawati, Andi; Darmawati, Darmawati (Universitas Patria Artha, 2020)
9,278 lives have been lost. 130,538 patients are still struggling. However, 85,831 people have proven that sick because of the new type of Corona Virus or COVID-19 can be cured. (Liputan6.com). In Indonesia, there were 12,438 cases of Corona virus infection with 895 people dying and 2,317 declared. The World Health Organization (WHO) has paid special attention to the special policies of a number of countries that have begun to ease lockdowns or lockdowns in their territories. (Sindonews.com May 7, 2020). As a result of this pandemic, the life of the Indonesian economy has become devastated. The service and trade sectors have become stagnant. So that many of us see and read in the mass media, termination of employment to informal sector workers because production is hampered. The social impact caused by this pandemic has become a serious concern of the government by forming a task force. This task force coordinated by the social service distributed social assistance to people affected by the Covid 19 outbreak. In terms of distribution of distribution, social services have involved all lines of government starting from the lowest line, as well as reporting of results, also involving all areas of supervision, one of which is the inspectorate